Analysis of The Concept of Mustadhafin In Surah al-Nisa Verse 75: A Hermeneutical Study of Farid Esak - Mohammad Irfan Farraz Haecal (Senarai: Journal of Islamic Heritage and Civilization, 2024)
This study aims to explain Farid Esack's views through the theory of Liberation Hermeneutics studying the Quran surah an-Nisa 75th verse. This research uses a literature study, using the documentative method. This research Farid Esack is present as an interpreter at this time who consistently clings to the Koran as the primary source of his research on the division of social classes that are low poor or oppressed using the concept of regularity of meaning in the Koran against the discussion of mustadh'afin. Farid Esack as a great man in fighting for the oppressed to know effectively the existence of God for His creatures. Interpreting the text of the Quran using a historical approach, and the conceptation uses the idea of the primacy of the position of the oppressed on the side of God and the Prophet. Commitment in humanism and solidarity as the point of shaping the search for the hermeneutics of Quranic pluralism for liberation.  The study recommends further research